RETRACTED: Adverse Pregnancy Outcomes Following Exposure to Biologics in Women With Crohn's Disease: A Systematic Review and Meta-Analysis - Wang, Han; Chen, Fang; Hu, Yue; Shen, Mengdie (Frontiers in Medicine, 2021)
Crohn's disease is a chronic disease, which commonly affects women during their reproductive years. Poorly treated Crohn's disease is associated with adverse pregnancy outcomes. Biologics, a group of therapeutic drugs targeting inflammatory mediators including anti-TNF, anti-integrins and anti-interleukins, are increasingly used in pregnant women with Crohn's disease, exposing both the women and their fetuses to treatment-related complications. At present, it is unclear which biologics are more superior. This study performed a systematic review and meta-analysis to assess the risk of adverse pregnancy outcomes in women with Crohn's disease after exposure to biologics. Bibliographic databases were searched from inception to May 2021. The outcomes of interest were preterm delivery, low birth weight, spontaneous abortion, and congenital abnormalities. A total of 11 studies comprised of 1,875 pregnancies among women with Crohn's disease were included. Of these, 1,162 received biologics and 713 received non-biologic therapy. During the remission phase of the disease, the use of biological therapy increased the risk of adverse pregnancy outcomes, of which anti-integrins were associated with a higher incidence of adverse pregnancy outcomes than anti-TNF and anti-interleukins. Systematic Review Registration:http://www.crd.york.ac.uk/PROSPERO, identifier: CRD42020191275.